PENGETAHUAN IBU TENTANG PENANGGULANGAN DIARE DENGAN PENATALAKSANAAN DIARE BALITA USIA 1-5 TAHUN: MOM'S KNOWLEDGE ABOUT MANAGEMENT OF DIARRHEA WITH MANAGEMENT OF DIARRHEA TO CHILDREN AGED 1-5 YEARS - Elsera, Chori; Rohmawati, Wiwin; Parmiyati, Parmiyati (Universitas Muhammadiyah Sidoarjo, 2015)
Mother's knowledge about prevention of diarrhea can cause diarrhea deteriorate that leads to death or getting better, depend on the management of diarrhea that mother do. The purpose of the present study is to find out the relationship between mother's knowledge on diarrhea prevention against treatment of diarrhea in children 1-5 years. This research method is a survey research with cross sectional approach and point-time models.The population of the study is all mothers who have children 1-5 years old in April 2015 amounted to 235 people. The sampling technique used was simple random sampling by lottery technique. The data is analyzing by Kendall tau. The results of the research are 22 respondents (46.8%) have good knowledge and management of diarrhea in children 1-5 years, 13 respondents (27.7%) have quite good knowledge and management of diarrhea in children 1-5 years, one respondent (2, 1%) lack of knowledge and management of diarrhea in children 1-5 years. There is a relationship between mother's knowledge on diarrhea prevention against treatment of diarrhea in children 1-5 years old at Jemowo village in 2015 with a p-value = 0.000 (p <0.05). The conclusion from this study showed there was relationship between mother's knowledge on diarrhea prevention against treatment of diarrhea in children 1-5 years old at Jemowo village in 2015. It is expected for mothers to increase knowledge and increase awareness in the prevention and treatment of diarrhea.